WHETHER THERE IS AN ASTROPHYSICAL SOURCE IN THE OSCILLATIONS OF GEOPHYSICAL PARAMETERS WITH A PERIOD OF 160 MINUTES? - Samsonov, S.; Miroshnichenko, L.; Kotov, V.; Skryabin, N.; Timofeev, V.; Baishev, D. (Одеські астрономічні публікації, 2013)
Oscillations with a period of 160 minutes in the ground pressure and Z-component of the geomagnetic field revealed by authors earlier are studied the regular ground measurements. For the analysis the data of five stations on the territory of Europe (Moscow, Apatity, Oulu) and Siberia (Yakutsk, Tixie) obtained in December, 2003 are used. It is shown that the specified oscillations revealed by authors earlier, are manifested in Europe andSiberiasynchronously. For December, 2003 the mean amplitude of oscillations in the ground pressure accounts for 0.012±0.002 mb; in a Z-component their value is equal to 0.323±0.070 nT. Authors discuss the possible nature of pulsations.